2004
DOI: 10.1063/1.1801991
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast excited-state dynamics in photochromic N-salicylideneaniline studied by femtosecond time-resolved REMPI spectroscopy

Abstract: Articles you may be interested inCommunication: Ultrafast time-resolved ion photofragmentation spectroscopy of photoionization-induced proton transfer in phenol-ammonia complex Ultrafast nonradiative dynamics in electronically excited hexafluorobenzene by femtosecond time-resolved mass spectrometry Ultrafast processes in photoexcited N-salicylideneaniline have been investigated with femtosecond time-resolved resonance-enhanced multiphoton ionization spectroscopy. The ion signals via the S 1 (n,*) state of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 45 publications
6
93
0
Order By: Relevance
“…9,[14][15][16][17]22,24,28,29 Theory predicts a ground-state torsion angle of 36°about the anil twist angle α (C 7 NC 6 C 5 dihedral angle; see Figure 1c for a definition of the critical angles considered in this study) at the B3LYP/6-31G* level of theory 28 and 44°at the HF/6-31G* level. 29 An angle of 49°was found by X-ray diffraction of crystalline SA.…”
Section: Introductionmentioning
confidence: 91%
“…9,[14][15][16][17]22,24,28,29 Theory predicts a ground-state torsion angle of 36°about the anil twist angle α (C 7 NC 6 C 5 dihedral angle; see Figure 1c for a definition of the critical angles considered in this study) at the B3LYP/6-31G* level of theory 28 and 44°at the HF/6-31G* level. 29 An angle of 49°was found by X-ray diffraction of crystalline SA.…”
Section: Introductionmentioning
confidence: 91%
“…Our experimental system for picosecond time-resolved study is described in several references. 45,63,64 Figure 4 displays the principle of picosecond time-resolved resonance-enhanced multiphoton ionization (REMPI) spectroscopy to measure the decays of the excited normal 7AI 2 dimer. The pump laser excites 7AI 2 in a specific single vibronic state of the normal dimer, subsequently the probe laser ionizes the normal dimer.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Regarding the ESIPT, fast kinetics experiments previously showed that it occurs both in solid state and in solution within 1 ps and 50 fs, respectively [24][25][26]. Even though the photochromism of anils was extensively studied in the past [24][25][26][27][28][29][30][31], some issues still exist regarding i) the existence of several excited species after the proton transfer (different cis-keto* isomers), ii) the nature of the precursor species of the final trans-keto photo-product and iii) their kinetics. Recently, different UV-visible ultrafast time-resolved experiments (transient absorption, fluorescence) on salicylidene aniline demonstrated that a hot cis-keto* is formed right after the ESIPT first which then relaxes to the fluorescent cold cis-keto* state [14,25,26].…”
Section: Introductionmentioning
confidence: 98%